Reversal of iron deficiency anemia-induced peripheral neuropathy by iron treatment in children with iron deficiency anemia - Kabakus, N; Ayar, A; Yoldas, TK; Ulvi, H; Dogan, Y; Yilmaz, B; Kilice, N (Oxford Univ Press, 2002)
The effects of iron deficiency anemia (IDA) on nerve conduction and efficiency of iron therapy were investigated by peripheral nerve-electrophysiological measurements. Eighteen children (10 boys, eight girls; mean age 31 +/- 1.3 months) with IDA and 12 healthy children (six boys, six girls; mean age 29 +/- 1.3 months) were enrolled into the study. Nerve conduction velocity was measured in the median and posterior tibial nerve. After nerve conduction values were determined in the patients and controls, 6 mg/kg/24 h ferrous sulphate was given orally to the patients for 3 months and nerve conduction velocity tests were performed again. Median/motor and sensory nerve conduction velocity and tibial/motor nerve distal-amplitute values of children with IDA were lower than for the control group (p < 0.05, p < 0.01 and p < 0.001 respectively). With iron supplementation these values increased to the normal levels and even higher than control levels for some parameters. In correlation studies between whole blood parameters and nerve conduction velocity results, there was a correlation between median/sensory nerve conduction velocity values and serum iron levels. Additionally there was a correlation between some nerve conduction velocity values and age. In conclusion, the evidence from this preliminary study suggests that peripheral neuropathy may develop in children with IDA. Peripheral neuropathy symptoms in these patients may be improved by iron therapy.
Keywords: Nerve-Conduction; Infants